A good man is hard to find: project management, entrepreneurship and serendipity. Issue 1 (4th March 2019) - Gartner, William B.
Abstract : Purpose: The purpose of this paper commentary is to explore the intersection of project management and entrepreneurship through a poetic exploration of Flannery O'Connor's short story: "A Good Man is Hard to Find." Through the use of the Japanese Haiku format, this commentary probes the nature and meaning of "projects, " the importance of goals and their limitations, the influence of context across time, and the role of agency and circumstance in entrepreneurship as denoted by the idea of serendipity. Design/methodology/approach: Poesis. Findings: Imagination steers the course. Vision sees the possibility; But the mind's eye sees through a distorted lens that is always misfit. So the unplanned path becomes the project. Always; Accidents happen. Originality/value: Project Management: Goals with temporary; Collective action; Entrepreneurship: "Organizing collective Action." Compromise?